Emission trading and overlapping environmental support: Installation-level evidence from the EU ETS - Klaas Mulier; Marten Ovaere; Leo Stimpfle (National Bank of Belgium, 2024)
We collect data on 24,000 state aid cases within the European Union to create granular measures of national environmental support and study their interactions with the European Union Emissions Trading System (EU ETS). Exploiting variation in regulated installations' exposure to carbon prices and an unexpected regulatory tightening of the EU ETS, we show that high exposed installations strongly reduced emissions relative to less exposed installations in the same industry with significant heterogeneity across countries and industries. In the power sector, emission reductions are significantly stronger in countries with more generous renewable energy support policies. In contrast, emission reductions in the manufacturing sector are significantly weaker in country-industries with more generous cost compensation for energy-intensive activities.
Keywords: D22; H23; L52; L98; Q48; Q54; Q58; 330; Cap-and-trade; Climate policy; Overlapping policies; EU ETS